The Effects of Inward Investment, Education, Internet Access, and ICT Index on Unemployment in Indonesia - Putra, Muhammad Rizky Karunia; Arif, Muhammad (Journal of Enterprise and Development (JED), 2026)
Purpose: This study examines the effects of inward investment, education level, internet access, and the Information and Communication Technology (ICT) Index on the unemployment rate in Indonesia.Method: This study applies a quantitative approach using panel data regression across 34 Indonesian provinces from 2019 to 2023, yielding 170 observations. The data were obtained from Statistics Indonesia (BPS) and the Ministry of Communication and Digital Affairs (Komdigi). Model selection was conducted using the Chow and Hausman tests, which confirmed the Fixed Effects Model as the most appropriate estimation method.Result: The findings show that inward investment and internet access negatively affect unemployment. This indicates that higher inward investment and broader internet access are associated with lower unemployment rates. Conversely, education level and the ICT Index positively affect unemployment, suggesting that improvements in education and ICT development have not yet been fully matched by labor market absorption across provinces.Practical Implications for Economic Growth and Development: The study highlights the need to improve the quality of investment by directing it toward job creation. It also emphasizes the importance of strengthening vocational education, aligning educational outcomes with labor market demand, and improving workforce digital skills to support inclusive and sustainable economic development.Originality/Value: This study integrates inward investment, education, internet access, and the ICT Index into a single analytical framework. Using provincial-level panel data, it offers a comprehensive perspective on unemployment dynamics, digital transformation, and regional labor market disparities in Indonesia.